원자력수용성 결정요인에서 개인, 지역, 국가 수준간 통합모형 분석 - 전세혁 (The Graduate School, Ajou University, 2024)
본 연구의 목적은 원자력 수용성에 대한 개인, 지역, 국가수준 분석에서 개인 인식과 객관적 지표를 통합하여, 원자력 수용성에 영향을 미치는 요인을 분석 하는 것이다. 개인과 지역수준은 우리나라를 대상으로 하며, 국가수준은 20개 국가를 대상으로 한다. 원자력수용성은 개인과 지역수준에서는 경제적수용성과 지역적수용성으로 설정하였고, 국가수준의 분석에서는 국제수준의 거시적 관점 을 고려하여 원전지지와 계속운영을 종속변수로 설정하였다. 또한 분석수준별 심층적 비교를 위하여 개인과 지역 표본은 수도권 여부, 원전과의 거리, 자연재 해 피해금액으로 분류한 분석을 진행하였고, 국가수준 분석에서는 원전의 운영 국여부, OECD회원국 여부, 온실가스배출량을 기준으로 표본을 분류하여 추가 적인 분석을 진행하였다. 개인수준 분석결과, 원자력 수용성에 영향을 미치는 주요 요인으로는 개인적 규범과 자기효능감이 가장 높은 상관관계를 보였다. 경제적 수용성에 대한 회 귀분석 결과, 비수도권 거주 표본들은 지각된 편익, 신뢰, 책임귀속, 개인적 규 범, 지진 경험, 후쿠시마 원전수 방류 행동, 자기효능감 등의 변수가 영향을 미 쳤으며, 수도권 거주 표본들은 지각된 편익, 신뢰, 책임귀속, 개인적 규범, 후쿠 시마 원전수 방류 행동 등의 변수가 유의미한 영향을 미쳤다. 원전과의 거리에 따른 분석에서도 유사한 결과가 도출되었으며, 자연재해 피해금액에 따른 분석 에서는 지각된 편익, 신뢰, 책임귀속, 개인적 규범, 지진 경험이 유의미한 변수 로 나타났다​. 지역수준 분석결과, 경제적 수용성에 영향을 미치는 주요 변수로는 편익, 신 뢰, 책임귀속, 개인적 규범, 지진 경험이 거주지역, 원전과의 거리, 자연재해 피 해금액 집단 모두에서 공통적으로 유의미한 영향을 미쳤다. 또한, 수도권에서는 지진 발생 건수가 경제적 수용성에 유의미한 영향을 미쳤으며, 이는 원전의 내 진 설계와 안정성 인식이 수도권 주민들에게 원자력의 안정성 인식을 강화시키 는 역할을 할 수 있음을 시사한다. 국가수준 분석결과, 국가 수준에서는 에너지 소비량, 국방 예산, 기후 위험 지 수, 1인당 GDP, 녹색당 점유율, 가정용 전력 가격 등이 원자력 수용성에 높은 상관관계를 보였다. 회귀분석 결과, 원전 운영 여부, OECD 회원국 여부, 온실 가스 배출량에 따라 원자력 수용성에 차이가 있었다. 원자력 에너지 지식은 원 전 운영국과 OECD 회원국에서 수용성에 긍정적인 영향을 미쳤으며, 이는 교육 수준과 정보 접근성이 원자력 수용성에 중요한 역할을 한다는 점을 강조한다. 본 연구의 함의는 첫째, 정부와 관련 기관은 투명한 정보 제공과 공정한 절 차를 통한 대중의 신뢰 제고 전략이 필요하다. 즉, 대중의 신뢰확보를 위해 정 기적인 정보 공개와 대중과의 소통을 통해 신뢰를 강화할 필요가 있다. 둘째, 대중이 원자력 에너지에 대해 객관적이고 정확한 지식을 습득할 수 있도록 학 교 교육과정에 원자력 관련 내용을 통합하고, 다양한 매체를 활용한 정보제공 활동이 필요하다. 셋째, 원자력 정책수립에 각 지역과 국가의 특성을 고려한 맞 춤형 접근이 필요하다. 예를 들어, 지진이 빈번한 지역에서는 내진 설계와 안전 성을 강조하고, 경제적으로 어려운 지역에서는 원자력 발전소가 제공하는 경제 적 혜택을 부각시킬 필요가 있다는 것이다. 본 연구의 한계는 다음과 같다. 첫째, 본 연구는 설문조사 데이터를 바탕으로 한 분석으로, 실제 행동과의 차이가 있을 수 있다는 한계를 가지고 있다. 둘째, EVE라고 명명한 변수들의 통합된 효과를 검증하지 못하였으며, 모든 지역적, 국가적 변수를 완벽히 반영하기 어려운 한계가 있다. 셋째, 개인인식과 객관적 지표데이터의 통합을 위한 방법론 적용이 이루어지지 않았다. 이를 보완하기 위해 추가적인 행동 기반 연구와 다양한 지역과 국가를 대상으로 한 후속 연구 가 필요하며, 이러한 보완 연구를 통해 원자력수용성 제고에 기여할 것으로 기 대한다. [주제어 : 원자력수용성, 기후변화대응, 지역적수용성, 국가적수용성, 에너지정책]|The purpose of this study is to analyze the factors affecting nuclear power acceptance by integrating personal perceptions and objective indicators in individual, regional, and national level analysis of nuclear power acceptance. The individual and regional levels are based on Korea, and the national level is based on 20 countries. Nuclear power acceptability was set as economic acceptability and regional acceptability at the individual and regional levels, and at the national level, the dependent variable was nuclear power plant support and continued operation, considering the macro perspective at the international level. In addition, we categorized individual, regional, and national samples for in-depth comparison by level of analysis._x000D_ At the individual level, the regression analysis of economic acceptability showed that the non-metropolitan sample was influenced by variables such as perceived benefits, trust, attribution of responsibility, personal norms, earthquake experience, Fukushima water discharge behavior, and self-efficacy, and similar results were found in the analysis by distance from the nuclear power plant. In the analysis by amount of natural disaster damage, perceived benefits, trust, attribution of responsibility, personal norms, and earthquake experience were significant variables._x000D_ At the regional level, the main variables affecting economic acceptability were perceived benefits, trust, blame attribution, personal norms, and earthquake experience, which were significant across all regions of residence, distance from nuclear power plants, and amount of natural disaster damage. _x000D_ Country-level analyses revealed differences in nuclear energy acceptance based on whether a country operates nuclear power plants, OECD membership, and greenhouse gas emissions. Nuclear energy knowledge had a positive effect on acceptance in nuclear power plant operators and OECD member countries, emphasizing that education level and access to information play an important role in nuclear acceptance. _x000D_ The implications of this study are that, first, governments and relevant organizations need strategies to increase public trust through transparent information provision and fair procedures. Second, to help the public acquire objective and accurate knowledge about nuclear energy, it is necessary to integrate nuclear energy-related content into school curricula and provide information through various media. Third, a customized approach to nuclear energy policy formulation is needed that takes into account the characteristics of each region and country. For example, emphasizing earthquake-resistant design and safety in earthquake-prone regions._x000D_ Limitations of this study include First, the analysis is based on survey data, which may not reflect actual behavior. Second, the combined effect of the variables named EVE was not verified, and it is difficult to fully reflect all regional and national variables. Third, no methodology was applied to integrate personal perceptions and objective metric data. Further behavioral-based research and follow-up studies in different regions and countries are needed to complement this study, which will contribute to the improvement of nuclear acceptance.
학위논문(박사)--과학기술정책학과,2024. 8
Keywords: 국가적 수용성; 기후변화 대응; 에너지 정책; 원자력수용성; 지역적 수용성